Reoperation Rates of Microendoscopic Discectomy Compared With Conventional Open Lumbar Discectomy: A Large-database Study. Issue 1 (15th January 2023) - Masuda, Soichiro; Fukasawa, Toshiki; Takeuchi, Masato; Fujibayashi, Shunsuke; Otsuki, Bungo; Murata, Koichi; Shimizu, Takayoshi; Matsuda, Shuichi; Kawakami, Koji
Abstract: Background: Microendoscopic discectomy for lumbar disc herniation has been shown to be as effective as traditional microdiscectomy or open discectomy in terms of clinical outcomes such as pain relief, and it is less invasive. Nevertheless, the reoperation rate for microendoscopic discectomy compared with microdiscectomy or open discectomy remains unclear, possibly due to difficulties in conducting follow-up of sufficient duration and in obtaining information about reoperation in other facilities. Questions/purposes: (1) What is the rate of reoperation after microendoscopic discectomy for primary lumbar disc herniation on a large scale at a median of 4 years postoperatively? (2) Is there any difference in revision rate at a median of 4 years and within 90 days postoperatively based on surgical method? Methods: We conducted a retrospective, comparative study of adult patients who underwent microendoscopic discectomy or microdiscectomy or open discectomy for lumbar disc herniation from April 2008 to October 2017 and who were followed until October 2020 using a commercially available administrative claims database from JMDC Inc. This claims-based database provided information on individual patients collected across multiple hospitals, which improved the accuracy of postoperative reoperation rates. We included 3961 patients who received microendoscopic discectomy or microdiscectomy or open discectomy between April 2008 and October 2017 in the JMDC claims database. After applying exclusion criteria, 50% (1968 of 3961) of patients were eligible for this study. Propensity score–weighted analyses were conducted in 646 patients in the microendoscopic discectomy group and in 1322 in the microdiscectomy or open discectomy group, with a median (IQR) of 4 years (3 to 6) of follow-up in both groups. Mean patient age was 42 ± 12 years in the microendoscopic discectomy group and 43 ± 12 years in the microdiscectomy or open discectomy group. Males accounted for 78% (505 of 646) of patients in the microendoscopic discectomy group and 79% (1050 of 1322) of patients in microdiscectomy or open discectomy group. The proportion of patients with diabetes mellitus in the microendoscopic discectomy group (10% [64 of 646]) was less than in the microdiscectomy or open discectomy group (15% [195 of 1322]). The primary outcome was Kaplan-Meier survivorship free from any type of additional lumbar spine surgery at a median of 4 years after the index surgery. The secondary outcome was survival probability using the Kaplan-Meier method with endpoints of any type of reoperation within 90 days after the index surgery. To determine which procedure had the higher revision rate, we conducted propensity score overlap weighting analysis, which controlled for potential confounding variables such as age, sex, comorbidities, and type of hospital as well as Cox proportional hazard models to estimate HRs and 95% confidence intervals (CIs). Results: The 5-year cumulative reoperation rate was 12% (95% CI 9% to 15%) in the microendoscopic discectomy group and 7% (95% CI 6% to 9%) in the microdiscectomy or open discectomy group. After controlling for potentially confounding variables like age, sex, and diabetes mellitus, the microendoscopic discectomy group had a higher reoperation risk than the microdiscectomy or open discectomy group (weighted HR 1.57 [95% CI 1.14 to 2.16]; p = 0.004). Within 90 days of the index surgery, after controlling for potentially confounding variables like age, sex, and diabetes mellitus, we found no difference between the microendoscopic discectomy group and microdiscectomy or open discectomy group in terms of risk of reoperation (weighted HR 1.38 [95% CI 0.68 to 2.79]; p = 0.38). Conclusion: Given the higher reoperation risk with microendoscopic discectomy compared with microdiscectomy or open discectomy at a median of 4 years of follow-up, surgeons should select microdiscectomy or open discectomy, despite the current popularity of microendoscopic discectomy. The revision risk of microendoscopic discectomy compared with microdiscectomy or open discectomy in the long term remains unclear. Future large, prospective, multicenter cohort studies with long-term follow-up are needed to confirm the association between microendoscopic discectomy and risk of reoperation. Level of Evidence: Level Ⅲ, therapeutic study.